PENGARUH FINANCIAL LEVERAGE, PROFITABILITY DAN CASH HOLDING TERHADAP INCOME SMOOTHING - Carolline, Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to empirically examine the influence of financial leverage, profitability and cash holding towards income smoothing in manufacturing companies listed in Indonesia Stock Exchange from period 2016– 2018. This study used 63 data from manufacturing companies that have been selected using purposive sampling method with total 189 data for three years. The data used are secondary data in form of financial statements. This research used Eviews version 10.0 software to process the data. The result of research shows that financial leverage and profitability have negative influence towards income smoothing. Cash holding has no influence towards income smoothing.